Awareness of Policyholders towards the Terms and Conditions of Life Insurance Policy - Ghimire, Rabindra; Ghimire, Shurendra (Journal of Interdisciplinary Studies, 2024)
Life insurance is a long-term investment and risk management tool. Yet policyholders often fail to recall the major attributes of the policy and its terms and conditions. The memory, understand and awareness towards the life insurance policy is influenced by various factors. The research aims to examine the association between the policyholders’ mental states, including their recall of policy characteristics, the value placed on policies, and their retained knowledge with the age and level of education. The study follows quantitative, descriptive, and cross-sectional research design. Data were gathered from 474 purposively selected policyholders in Gandaki and Bagmati Province using structured questionnaires. Descriptive and inferential tools were employed for analysis. Most policyholders are unaware of the maturity period of their policies, while only 2% cannot recall the purchased year. Memory of terms like premium waivers shows weak correlations, with even weaker links for other contract details. Out of seven tested associations, age has been found to be an insignificant factor, but education significantly influenced recall of some policy aspects. Many policyholders neglect reading terms and conditions, relying heavily on agents or relatives. Factors such as forced selling, policy complexity, and overconfidence in insurers contribute to this behavior, as explained by Cognitive Dissonance Theory. Policyholders tend to avoid engaging with contract details to reduce psychological discomfort, leading to insufficient understanding and potential loss of benefits. The findings emphasize the need for insurers to implement better education and communication strategies to enhance policyholders’ awareness and engagement with their insurance products.